Emotional Intelligence in the Personality of Leaders Based on the Paradoks Novel by Affifudin Omar - Hamzah, Nordiana (Malay Literature, 2025)
This study aims to examine the role of emotional intelligence in shaping the personality of a leadership figure in the novel Paradoks, using two main theoretical frameworks: Daniel Goleman’s theory of emotional intelligence and Sigmund Freud’s theory of personality. The research problem arises from the fact that the emotional and psychological aspects of leadership in Malay literary works have received limited attention, even though analyzing the inner dimensions of a character can enrich the understanding of leadership grounded in humanistic values. The leader figure in Paradoks exhibits inner conflicts, moral dilemmas, and struggles between instinct and reason, reflecting the balance between the id, ego, and superego. Therefore, this study analyzes how the five components of Goleman’s emotional intelligence, self-awareness, self-regulation, self-motivation, empathy, and social skills interact with Freud’s three personality layers (id, ego, and superego) in shaping an effective and ethical leadership style. The study employs a qualitative approach with a textual analysis design, focusing on the novel Paradoks as the primary data source. A checklist derived from both theories is used to ensure that the analysis is conducted systematically and structurally. The findings indicate that a balance between emotional intelligence and the layers of personality plays a crucial role in shaping the integrity, humanity, and visionary outlook of the leader figure. In conclusion, the integration of emotional intelligence theory and personality theory provides a significant framework for understanding leadership in Malay literature and contributes to the development of leadership discourse based on psychology and humanistic values. Keywords : emotional intelligence, leader personality, id, ego, superego and Malay literature. Full text:   PDF